Persistence of bureaucratic overrepresentativeness or under-representativeness: experience of the civil service in Malaysia - Yashaiya, Nadia Hezlin; Noh, Malaysia (2019)
What contributes to the persistent nature of bureaucratic over-representativeness or under-representativeness? Answers to such a question are necessary because, while there have been many empirical studies of the relationship between different types of bureaucratic representation (gender, ethnic, class) and/or different features of bureaucracies (levels, types of agencies, unitary or federal) and possible policy outcomes, the studies have largely been silent when it comes to identifying antecedents to bureaucratic over-representativeness or under-representativeness. Accordingly, by studying Malaysian experience involving a largely mono-ethnic bureaucracy in a highly plural and fragmented society, this discussion identifies factors that have contributed to the persistent nature of an under-represented and over-represented bureaucracy. The underlying findings are that there is a need to move away from a monolithic argument that mono-ethnic representation of the bureaucracy is solely due to a state’s interventionist policy, and that the stickiness of administrative tradition, perception, socialisation and attractiveness of alternative sectors of employment can contribute to the persistent nature of bureaucratic representation.